Turismo, paisaje y medio ambiente. Reflexiones geográficas - Faus Pujol, M. Carmen; Higueras Arnal, Antonio (Geographicalia, 2016)
Today, tourism has become a phenomenon of masses, whose economic, cultural and social significance is not denied by anyone. In some countries, such as Spain, tourism has become the contry's "main industry», due to the amount of its contribution to the GNP. Therefore, the majority of the developing countries try to foster tourism, offering an enormeous variety of incentives, either natural or cultural. However, a shadow is cast over the friendly side of tourism, which is usually the economic one, by the damage that massive and uncontrolled tourism causes to the environment and which, at times, threatens to destroy it in the short run; when it becomes a speculative activity of the natural medium and not of is use. To avoid the destruction of the tourist "resource" the tourist activities must be planned so that the effect of the speculation of the environment,which sun and beach tourism generally becomes, is counteracted by the production of natural values that the natural medium contains.
Keywords: Tourism; landscape; environmental degradation